Effect of Reward, Work Environment, and Motivation towards Performance of the Millennial Generation in the Central Bureau of Statistics of East Kalimantan Province - MT, Indah Cahyani; Rahmawati; Milwan (LPPM Universitas Terbuka, 2021)
A success of a work organization is strongly influenced by employee performance. To achieve this success requires a strong foundation from its employees, including the motivation that can be supported from the work environment and awards given by the organization. For the Central Bureau of Statistics in the Province of East Kalimantan, this is a challenge to achieve higher work performance and compete with other districts / cities in Indonesia. This study aims to analyze the influence of the work environment and appreciation of motivation and the effect of motivation on performance on Millennial Generation within the Central Bureau of Statistics of East Kalimantan Province. The population in this study were all employees of the Central Bureau of Statistics of East Kalimantan Province. Whereas the sample are employees of the Central Bureau of Statistics of East Kalimantan Province with age constraints of 25-40 years (129 samples). The data was collected using an electronic questionnaire to the respondents. To answer the problems in research and testing of research hypotheses, it uses Structural Equation Modeling (SEM) analysis by using Partial Least Square (PLS) with the help of SmartPLS 3.0 software. The results of this study indicate that (1) award influences motivation on Millennial Generation in the environment of Central Bureau of Statistics of East Kalimantan Province (2) work environment influences motivation on Millennial Generation in the environment of Central Bureau of Statistics of East Kalimantan Province (3) motivation influences performance on Millennial Generation in the environment of Central Bureau of Statistics of East Kalimantan Province (4) awards, work environment, and motivation affect the performance of the Millennial Generation in the environment of Central Bureau of Statistics of East Kalimantan Province.